PENGARUH PROMOSI MEDIA SOSIAL DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN FLORIST DI KOTA BANGKINANG - Irawan, Andri; Putri, Librina Tria; Henrizal, Henrizal (STIE Bangkinang Publishing, 2022)
This research was conducted with the aim of examining the Influence of Social Media Promotion and Word Of Mouth on Florist Consumer Purchase Decisions in Bangkinang City and the variables that influence Florist Consumer Purchase Decisions in Bangkinang City. The population in this study are consumers who make purchasing decisions on Florists in Bangkinang City. non-probability sampling technique, namely purposive sampling. Purposive sampling is a sampling technique with certain considerations. The sample that is set in this research is based on the calculation results, it is known that the number of samples is 96 respondents. Hypothesis testing using multiple linear regression analysis with the help of SPSS 23.00 for windows. The results showed that simultaneously and partially Social Media Promotion and Word Of Mouth. Influence on Florist Consumer Purchase Decisions in Bangkinang City.